Historical-Demographic Dynamics of Medieval Azerbaijan: A Comparative Historiographical Examination of Population Structure, Ethnicity, Migration, and Socio-Political Transformations (Architecture Image Studies, 2025)
In recent decades, demographic history has emerged as a critical field for understanding long-term socio-political and economic developments within complex societies. Global processes—ranging from climate change and land degradation to increasing pressure on natural resources and rising food insecurity—have intensified scholarly interest in historical population dynamics as a foundation for contemporary demographic theories. While significant attention has been devoted to demographic transitions in Europe and the Islamic world, the historical-demographic trajectory of the Azerbaijani lands during the Middle Ages remains comparatively under-researched in international scholarship. This study conducts a comprehensive historiographical analysis of Azerbaijani demographic realities in the medieval era by examining works produced by Azerbaijani, Turkish, Persian, Russian, and Western historians. It investigates key dimensions such as population size and density, ethno-linguistic composition, urban and rural settlement structure, migratory patterns, socio-economic transformations, and state-level demographic policies. By situating medieval Azerbaijani demography within the broader Eurasian geopolitical and cultural context, the research highlights the dynamic interplay between nomadic and settled populations, the impact of trade and warfare on population movements, and the influence of Islamic legal-ethical thought on family structure and fertility trends. The analysis demonstrates that medieval demographic thought in Azerbaijan evolved at the intersection of Islamic social philosophy, Turkic cultural traditions, and regional geopolitical realities. Unlike certain Western medieval philosophies which viewed population expansion as a potential cause of scarcity and social instability, scholars of the medieval Muslim East perceived population growth as a divine blessing and a driver of social vitality and economic productivity The study concludes that medieval demographic processes in Azerbaijan played a foundational role in shaping the region’s ethno-political identity, settlement geography, and cultural continuity.